Advances and innovations in university assessment and feedback : a festchrift in honour of Professor Dai Hounsell - Kreber, Carolin; Anderson, Charles, 1952-; Entwistle, Noel James; McArthur, Jan; Hounsell, Dai (Edinburgh University Press, 2014)
Our understanding of the purposes of assessment and the nature of assessment practices in higher education has changed markedly over the past forty years. These changes are a response not only to recent developments in our conceptualisations of student learning but also to the demands a rapidly changing and increasingly complex world places on students. This book contains new perspectives on assessment and feedback provided by world renowned researchers on issues that are currently of great interest to both academic managers and teaching staff, as they try to make courses more effective and more appealing at a time when universities compete for incoming students. Rather than simply sharing recent inventions in assessment and feedback, the contributors to this book highlight the linkages between these innovations and new theorising and empirical research on assessment and student learning, thereby offering practices that are not only pioneering but evidence-based. Key Features. Provides a historical overview of assessment and feedback in universities showing how our understanding of assessment practices has changed over the years, both in response to new conceptualisations of learning and the changing nature of society Contains new perspectives of assessment and feedback provided by world renowned researchers on issues that are currently of great interest to both academic managers and teaching staff Reports on recent innovations in assessment practices in higher education Engages critically with recent research on assessment and feedback offering evidence-based conclusions